Radiation pattern reconfigurable antenna for LTE applications - Kumar, Gorantla Dileep (2018)
This project proposes a radiation pattern reconfigurable antenna for LTE applications. Long Term Evolution (LTE) is an advanced system in the wireless telecommunication development. Compared to previous standards, LTE offers improved performance. The main advantage of this project is to steer the radiation pattern to a particular direction. The radiation pattern steering is achieved by applying progressive phase shifting. The transmission line model is used to obtain design parameters of the antenna. By using the progressive phase shift concept, three different configurations of patch array antennas are designed at 2.6GHz operating frequency. The three different directions had been formed at -15°, 0°, 15°. FR4 substrate is used for designing the reconfigurable antenna with thickness of 1.6mm. Measured and simulated results are well matched, but with some minor deviations. The gain of the antenna is 4.4dB with broadside direction and the gain is 4.6dB when the beam steers to either ±15°.